(untitled) - India; Ministry of Food and Agriculture (India, 1960)
This book introduce about birth of a new idea, preliminary plans, mounting of the camaign, new method gains ground, achievements and the future, work in the states.
Keywords: Cải cách nông nghiệp,Agricultural innovations; Ấn Độ,India